Pengaruh Pembelajaran Mendalam Berbasis Problem Based Learning terhadap Kemampuan Pemecahan Masalah Matematis Siswa Kelas X - Aini, Ida Nur; Sulistyaningrum, Heny (Jurnal PEKA (Pendidikan Matematika), 2026)
This study analyzes the impact of implementing the Problem Based Learning (PBL) model, which emphasizes deep learning, on students' mathematical problem-solving skills, given the ongoing difficulties faced by tenth-grade students at SMAN 3 Tuban in the 2025/2026 academic year regarding selecting critical information, synthesizing concepts, and applying knowledge to real-world situations. Utilizing a quantitative approach with a quasi-experimental, nonequivalent control group design, this research assesses the effectiveness of the model by assigning class X-D as the experimental group and X-E as the control group, each comprising 36 students selected via cluster random sampling. Data processing was conducted using normality tests, homogeneity tests, and Independent Sample t-tests based on the results of pretest and posttest essay assessments. The findings indicate that H₀ is rejected and H₁ is accepted, with the mean posttest score of the experimental group significantly outperforming that of the control group at a significance level of 0.000 (< 0.05), thereby confirming that the deep learning-oriented PBL model has a significant impact on enhancing students' mathematical problem-solving proficiency.